Effect of different polyol solvents on the synthesis of CuInS2nanoparticles by cyclic microwave irradiation - Nawapong Chumha (2018)
© 2017, Hanyang University. All rights reserved. CuInS 2 nanoparticles were synthesized by a cyclic microwave irradiation method at 600 W for 75 cycles. The effect of different polyol solvents (ethylene glycol, glycerol, and propylene glycol) on the synthesis of the CuInS 2 nanoparticles was investigated. Characterized by XRD, the powders synthesized using ethylene glycol and glycerol were pure CuInS 2 with tetragonal structure. However, CuInS 2 with the existence of CuS was obtained when using propylene glycol due to the lower resulting reaction temperature. FTIR spectra of the residual solvents after the synthesis process were determined and this revealed that ethylene glycol and glycerol were the solvents with good reducing capability. FESEM images revealed that the synthesized CuInS 2 powders were composed of nanoparticles with diameters in the range of 20-100 nm. The CuInS 2 nanoparticles synthesized using glycerol were smaller than those synthesized using ethylene glycol, due to the higher viscosity of glycerol.